2011
DOI: 10.2319/090310-519.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading activates β-catenin signaling in periodontal ligament cells

Abstract: The Wnt/β-catenin signaling pathway components are functional and activated by mechanical loading in PDL cells. β-catenin serves as an effector of mechanical signals in PDL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
(38 reference statements)
4
27
0
Order By: Relevance
“…It is not clear if β-catenin is responsible for bone maintenance in response to loading, plays a role in mechanotransduction in alveolar bone around teeth, or plays a role in the functions of the PDL. Supporting evidence shows β-catenin expression in the PDL in mice (Lim et al, 2014, Premaraj et al, 2011) in addition to being present in osteocytes and cementocytes. A recent study using PDL stem cells showed that β-catenin could regulate osteogenic differentiation in inflammatory microenvironments through inhibition of the noncanonical Wnt pathway, which is similar to the regulation by β-catenin of bone homeostasis (Liu et al, 2011).…”
Section: Role Of β-Catenin Signaling In the Periodontal Ligament (mentioning
confidence: 89%
See 1 more Smart Citation
“…It is not clear if β-catenin is responsible for bone maintenance in response to loading, plays a role in mechanotransduction in alveolar bone around teeth, or plays a role in the functions of the PDL. Supporting evidence shows β-catenin expression in the PDL in mice (Lim et al, 2014, Premaraj et al, 2011) in addition to being present in osteocytes and cementocytes. A recent study using PDL stem cells showed that β-catenin could regulate osteogenic differentiation in inflammatory microenvironments through inhibition of the noncanonical Wnt pathway, which is similar to the regulation by β-catenin of bone homeostasis (Liu et al, 2011).…”
Section: Role Of β-Catenin Signaling In the Periodontal Ligament (mentioning
confidence: 89%
“…With the osteocalcin-Cre; Wntless fl/fl mice (Wntless, a conserved membrane protein gene dedicated to the secretion of Wnt proteins), a pathological widening of the periodontal ligament space is observed with this elimination of Wntless in teeth (Lim, Liu, 2014). An in vivo study using human PDL cells showed responses to the activation of β-catenin via LiCl, leading to intensive β-catenin nuclear translocation (Premaraj, Souza, 2011). With loading on the human PDL cell, the activation of β-catenin was increased and inhibition of FAK suppressed β-catenin, suggesting that β-catenin mediated mechanotransduction in PDL (Premaraj et al, 2013).…”
Section: Role Of β-Catenin Signaling In the Periodontal Ligament (mentioning
confidence: 99%
“…This was a transient response because after the recovery period post-load, β-catenin was localised to the cytoplasm only. This is the first report of the mechano-responsiveness of β-catenin in chondrocytes, although mechanical activation of β-catenin signalling has been reported in the colon of APC 1638N/+ mice [26], mesenchymal stem cells [27] and periodontal ligament cells [28]. In contrast to the Wnt3A stimulated cells, where β-catenin is almost completely nuclear, an additive effect of load and Wnt3A on β-catenin localisation was observed with extensive β-catenin detected in the nucleus and throughout the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signalling is an important signalling cascade in myogenesis, regulating proliferation and satellite cell fate (reviewed in 145 ). In periodontal ligament cells (PDL), compressive stress leads to the activation of Wnt/B-catenin signalling pathway 146 , similar to in vivo compression of murine osteoblasts 147 . Exposing murine osteoblasts to shear flow upregulates Wnt pathways associated genes 148 , whereas exposing several colon cancer cell lines to shear flow inhibits Wnt/B-catenin activity 149 .…”
Section: Mechanical Loads -Stretch and Shear Forcesmentioning
confidence: 99%